Young justice. 3-pack fun [videorecording (DVD)] (Warner Home Video, 2012)
The first 12 episodes show how it all began. How Robin, Kid Flash and Aqualad are first invited into the Hall of Justice, how they help save Superboy from a genetics lab, and how the recruits crash their new base in Mt. Justice to join forces with some real girl power: Miss Martian and Artemis. As they train together and learn to trust one another, it's not always easy, the heroes take on some serious forces of evil in the form of super-powered androids, brainwashed genomorphs and more.